Relevance of nano- and microplastics for freshwater ecosystems: A critical review - Triebskorn, Rita; Braunbeck, Thomas; Hanslik, Lisa (Trends in analytical chemistry, 2019)
The current paper critically reviews the state-of-the-science on (1) microplastics (MP) types and particle concentrations in freshwater ecosystems, (2) MP and nanoplastics (NP) uptake and tissue translocation, (3) MP/NP-induced effects in freshwater organisms, and (4) capabilities of MP/NP to modulate the toxicity of environmental chemicals. The reviewed literature as well as new data on MP and NP concentrations in the river Elbe and on particle uptake into human cells indicate an environmental relevance of small particles in the low nano- and micrometer range higher than that of larger MP.